Uganda Christian University - Muhindo Miriam Nyabagheni (Uganda Christian University, 2024)
The financial status influences the academic performances of students at university levels. It was a case study that involved BBA3:2 students at Uganda Christian University. In the light of the above, the research sought to look into some of the variables that included family income and academic achievement, access to educational resources and educational outcomes, peer socio-economic differences and parental involvement and performance. The methodology adopted for the survey was a form of cross-sectional survey. Regarding this, 160 UCU BBA3:2 Students filled out questionnaires. This data analysis has been done through SPSS, version 20, and thereby extracting all the possible Pearson correlations and necessary descriptive statistics, to scan this relationship. It also showed that there was a moderate negative correlation between income of the family and academic achievement, as evidenced by the Pearson correlation coefficient of -0.385 with a significance level of 0.002, thus hinting that the better the income of the family, the lower perhaps the performance. On the other hand, opportunities for educational resources, such as technology and extracurricular activities, were found to positively relate to improvements in academic outcomes. The finding underlines the role played by these resources in enhancing the educational experiences of students. While parental involvement appeared to be most influential in improving academic achievements with the average of 4.01 points, reflecting very positive consequences, academic results on the other side were influenced by socio-economic difference of a peer but to much lesser degree reflected in the average of 3.03 points. These findings are in agreement with the literature review that underlined parental support and resource availability for academic outcomes. This leads the study to deduce that higher family income results in lower academic achievement-a suspicion that other factors than financial resources at home, such as family expectations and support structures, may be at play. These findings from this study call for targeted academic support for students coming from low-income backgrounds, guaranteed equal access to educational resources, and increased parental involvement in the students' academic lives.